Feasibility and acceptability of inserts promoting virtual overdose monitoring services (VOMS) in naloxone kits: a qualitative study - Fahad Safi; William Rioux; Nathan Rider; Barbara Fornssler; Stephanie Jones; S. Monty Ghosh (BMC, 2023)
Abstract Background In response to the ongoing opioid epidemic, there have been efforts to develop novel harm reduction strategies alongside scaling of currently implemented programs. Virtual overdose monitoring services (VOMS) are a novel intervention which aims to reduce substance-related mortality through technology for those who are out of reach of current supervised consumption sites. Scaling of naloxone programs presents a unique opportunity to promote VOMS to people at risk of substance-related mortality. This study aims to explore the feasibility and acceptability of naloxone kit inserts in promoting awareness of VOMS. Method We used purposive and snowball sampling to recruit 52 key informants, including people who use drugs (PWUD) with experience using VOMS (n = 16), PWUD with no prior experience using VOMS (n = 9), family members of PWUD (n = 5), healthcare and emergency services professionals (n = 10), community-based harm reduction organizations (n = 6), and VOMS administrators/peer support workers (n = 6). Two evaluators completed semi-structured interviews. Interview transcripts were analyzed using thematic analysis informed to identify key themes. Results Four key interrelated themes emerged, including the acceptability of naloxone kit inserts to promote VOMS, best practices for implementation, key messaging to include within promotional materials and facilitators to dissemination of harm reduction material. Participants highlighted that messaging should be promoted both inside and outside the kits, should be concise, provide basic information about VOMS and can be facilitated through current distribution streams. Messaging could further be used to draw attention to local harm reduction services and could be promoted on other supplies, including lighters and safer consumption supplies. Conclusion Findings demonstrate that it is acceptable to promote VOMS within naloxone kits and highlight interviewees preferred ways to do so. Key themes that emerged from interviewees can be used to inform the dissemination of harm reduction information, including VOMS and bolster current strategies for reducing illicit drug overdose.